Study The Lung-Protective Effects of Riboflavin and Cyanocobalamin Against Lung Toxicity-Induced by Cyclophosphamide in Rats - ghanim, waleed khalid; Muhsin S. G. Al-Moziel; Hussein M. Abood (Iraqi Journal of Pharmaceutical Sciences, 2023)
Cyclophosphamide (CP) is a cytotoxic alkylating agent it’s used associated with different side effects including lung toxicity. Vitamin B2 and vitamin B12 have lung-protective effects. This study was designed to evaluate lung-protective effects of both vitamins against lung toxicity induced by cyclophosphamide. seventy healthy adult albino male and female rats divided into seven groups each group containing ten rats were used in the present study and treated for seven days. On day eight rats were sacrificed and serum was obtained for glutathione and total antioxidant capacity measurement and lung extracted for immunohistochemical study; both vitamins significantly (P<0.05) increased glutathione and total antioxidant capacity in comparison with group two and improve immunohistochemical changes in comparison with the group treated by cyclophosphamide only